English Students’ Character Reflected in Teaching and Learning of Seminar on Linguistics Course - Haryanti, Sri; Setyandari, Ana (International Journal of Active Learning, 2020)
This study aims to describe the students’ character reflected in Seminar on Linguistics course. The students’ character is limited to seven (7) types, namely: respect, honesty, courage, confident, communicative, curious, and cooperative. This course must be taken by VII semester students of the English Education Study Program, Teacher Training and Education Faculty, University of Widya Dharma Klaten. This course was attended by eighteen (18) students and guided by one (1) lecturer who became the source of research data. The research data are in the form of the results of notes on the teaching and learning process of Seminar on Linguistics which were collected by directly observing the teaching and learning process of Seminar on Linguistics. The collected data were analyzed by statistical method especially the mean value. The students’ character is measured by the rubric. The result of the analysis shows that the students’ character reflected in Seminar on Linguistics course is very good with a mean value of 17.